ANALYSIS OF POSTOPERATIVE COMPLICATIONS IN THE SURGICAL TREATMENT OF PROXIMAL HUMERAL FRACTURES IN PATIENTS WITH DECREASED MINERAL BONE DENSITY - Makarov, Vasyl; Korzh, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Objective. To conduct a comparative retrospective analysis of the impact of postoperative complications on functional outcomes following different surgical treatment methods for proximal humeral fractures of AO/OTA types 11-B and 11-C in patients over 45 years old with decreased bone mineral density. Methods. The study analyzed the surgical treatment outcomes and postoperative complications in 102 patients aged (61.1 ± 8.1) years, who were divided into three groups based on the treatment method: (1) open reduction and internal fixation (ORIF) using a PHILOS plate (n = 50); (2) ORIF with a PHILOS plate combined with 3D-printed PLA implants (n = 44); (3) primary reverse total shoulder arthroplasty (RTSA) using a newly developed total reverse endoprosthesis (n = 8). Functional outcomes in patients with complications were assessed using the Constant-Murley Score at 3, 6, and 12 months postoperatively and analyzed based on individual preoperative parameters and treatment methods. Results. A total of 30 postoperative complications were recorded, the most common being superficial infection (7.8 % of the total population), secondary displacement (6.9 %), varus malalignment of fragments (6.9 %), and avascular necrosis of the humeral head (3.9 %). The highest number of complications was observed in Group (1), with 19 patients affected, accounting for 38 % . For all complications except avascular necrosis, a significant improvement in functional outcomes was observed between 3 and 12 months postoperatively. The mean Constant-Murley Score in patients with complications at 12 months postoperatively was (78.7 ± 8.5). Conclusions A retrospective analysis of postoperative complications following different surgical treatment methods established that, compared to other options, reverse total shoulder arthroplasty (RTSA) is a modern and optimal surgical treatment option for proximal humeral fractures of AO/OTA types 11-B or 11-C in the context of severe bone mineral density reduction, particularly in elderly patients.